mind sharp

if f ( x ) = x 6 + 10 x 5 + 10 x 4 + 10 x 3 + 10 x 2 + 10 x + 10 f(x)=x^{6}+10x^{5}+10x^{4}+10x^{3}+10x^{2}+10{x} +10 then find f ( 11 ) f(11) .


The answer is 3543121.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rewrite 10 = x 1 10 = x-1 . Then f ( x ) = x 6 + ( x 1 ) ( x 5 + x 4 + + x 0 ) = x 6 + ( x 6 1 ) = 2 x 6 1. f(x) = x^6 + (x -1)(x^5 + x^4 + \cdots + x^0) = x^6 + (x^6 - 1)= 2x^6 - 1. Use a calculator for the rest.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...